Evaluation of Security Techniques in Heterogeneous IoT Devices - Mosca, Eduardo E. P.; Ribeiro, Silvio; Urbano, Arthur; Silva, Danielle S.; Gomes, Rafael L. (Companion Proceedings of the Latin-American Symposium on Dependable and Secure Computing (LADC); 2022: Companion Proceedings of the 11th Latin-American Symposium on Dependable Computing, 2022)
The evolution of micro-controllers has enabled the diffusion of Internet of Things (IoT) devices in any kind of environment, including industrial environments. However, those devices still lack security solutions, once it has lower computational resources, hampering the application of techniques like Hashing Algorithms and Anonymization Techniques. In this context, this practical experience report aims to identify the viability of Hashing and Anonymization Techniques in IoT devices to increase reliability and evolve the security level, such as the do not overload the resources which are already limited. This identification was realized through real experimentation with two IoT devices (ESP8266, and ESP32) and an analysis of collected data. Through the experiments it was possible to identify the applicability limit of these hashing and anonymization techniques to support security solutions, when IoT devices are considered, proposing a benchmark for security in IoT.